Sciatic nerve injection palsy in a dog: Electrodiagnostic testing and microsurgical treatment - Mortari, Ana Carolina; Quitzan, Juliany Gomes [UNESP]; Brandão, Claudia Valéria Seullner [UNESP]; Rahal, Sheila Canevese [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: Iatrogenic damage to the ischiatic nerve is considered uncommon and may cause dysfunction with variable clinical signs dependent on type and severity of injury. Due to important role of this nerve in locomotion and weight-bearing limb, a poor prognosis for recovery may be observed in many cases. Electromyography analysis may suggest the neuroanatomic localization, diagnosis information, and severity of lesion to determine better therapeutic intervention. Therefore, the aim of this report is to describe the possible cause, diagnosis and treatment of a postinjection ischiatic nerve injury in a dog with complete recovery. Case: A 3-year-old neutered male dachshund dog was referred to the Veterinary Hospital due to inability to weight support in the right hind limb after diminazene diaceturate intramuscular injection. The gait evaluation showed dropped-hock and knuckling into the digits of the right hind limb and neurologic examination revealed moderate muscle atrophy below to femorotibial joint of the right hind limb with sensory analgesia (superficial and deep) on the lateral, dorsal, and plantar surfaces, absent patellar reflex, and proprioceptive deficit. Electrophysiologic testing was done under general anesthesia in a 2-channel Nicolet Compass Meridian apparatus. Absence of compound muscle action potentials after right fibular and tibial nerve stimulations, and abnormal spontaneous activity in cranial tibial, gastrocnemius and deep digital extensor muscles were observed. A diagnosis of moderate/severe axonotmesis of sciatic nerve was achieved. Under microscope magnification, all adherent adjacent tissue and epineural sheat were removed. Due this, a small epineural window was created. On neurological examination performed 30 days after surgery, complete recovery of sensitivity of the right hind limb, and normal proprioception were observed. The muscle atrophy was also noted to have improved. Discussion: The ischiatic nerve mechanisms of injury include direct needle trauma, the drug or vehicle used for injection, or secondary constriction by scar, factors that may be associated to damage nerve observed in the present case. During a sciatic nerve injection, the combination of intrafascicular placement of a needle and high-pressure injection may cause severe fascicular damage and persistent neurologic deficits. In the present case, damage to the nerve probably was not caused by the injection needle, but due to injection agent. Chemical irritation or toxic reaction to the agent may cause different degrees of nerve injury. The electrophysiologic testing is an important tool for determining alteration of function and integrity of the axonal motor unit. In the present report, the electrophysiologic testing showed denervation potentials in the muscles innervated by the sciatic nerve (positive waves and fibrillation potentials), and the absence of compound muscle action potentials was indicative of severe axonal damage of the right ischiatic nerve. In human patients with postinjection ischiatic nerve injury, early surgical treatment with neurolysis or resection and anastomosis are the procedures recommended. In the present report, external neurolysis and epineural window were used showing excellent functional results. The epineural window was performed due to adherence of tissue and scar surrounding the nerve, permitting neural decompression.
Keywords: Axonotmesis; Dogs; Neurolysis; Neurophysiology